Propulsive efficiency and non- expert swimmers performance - T.M. Barbosa; V. Lima; E. Mejias; M.J. Costa; D.A. Marinho; N. Garrido; A.J. Silva; J.A. Bragada (Desafio Singular, 2009)
Propulsive efficiency is one of the most interesting issues for competitive swimming researchers, has it presents significant relationships with the swimmer's biophysical behavior and his/her performance. Although propulsive efficiency is a variable that has been quite studied in elite swimmers, there is no research on this issue in young and non-expert swimmers. Thus, the aim of this study was to: (i) estimate the propulsive efficiency on non-expert swimmers; (ii) identify biomechanical and anthropometrical parameters that are associated with propulsive efficiency; (iii) identify the association between the propulsive efficiency and swim performance. Twenty-eight non-expert swimmers participated on this study. It was assessed the propulsive efficiency, biomechanical and anthropometrical parameters, as well as, the swim performance. The propulsive efficiency of non-expert swimmers is lower than data reported in the literature to higher competitive levels swimmers and there are no significant differences between boys and girls. It was also noted that several biomechanical and anthropometrical parameters, as well as, the swim performance are associated with the propulsive efficiency.